Pengaruh Employee Stock Option Plan pada Kinerja Perusahaan dan Implikasinya pada Return Saham - Trisna, Ricci Nurly; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2018)
ESOP is a program to give employee a chance to have company stock. In order to increase performance. The increasing employee performace, it’s can increasing company performance too. This study aims is for knowing the effect Employee Stock Option Plan on company performance and the implications on stock return. The total sample as much as 34 company, with method is purposive sampling. The data analysis technique be use is multiple linier regression. First hypothesis testing results is ESOP have positive effect to company performance. The second hypothesis testing results show that ESOP have positive effect to stock returns. The third hypothesis testing results show that company performance have positive effect to stock returns. The fourth hypothesis testing result show that company performance partially have significant effect to stock returns. Keywords: ESOP, Company Performace, Stock Returns